2022
DOI: 10.3389/fchem.2022.905794
|View full text |Cite
|
Sign up to set email alerts
|

A method to map the interaction network of the nuclear lamina with genetically encoded photo-crosslinkers in vivo

Abstract: Lamins are intermediate filaments that assemble in a meshwork at the inner nuclear periphery of metazoan cells. The nuclear periphery fulfils important functions by providing stability to the nuclear membrane, connecting the cytoskeleton with chromatin, and participating in signal transduction. Mutations in lamins interfere with these functions and cause severe, phenotypically diverse diseases collectively referred to as laminopathies. The molecular consequences of these mutations are largely unclear but likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Characterization of the binding process led to the finding that VCP/p97 plays a crucial role in regulating IFITM3 trafficking, turnover, and activity. In a recent study, Bpa was incorporated into laminC variants to study the network of interacting proteins at the nuclear lamina in live mammalian cells (Neumann‐Staubitz et al, 2022 ).…”
Section: Genetically Encoded Photo‐crosslinkersmentioning
confidence: 99%
“…Characterization of the binding process led to the finding that VCP/p97 plays a crucial role in regulating IFITM3 trafficking, turnover, and activity. In a recent study, Bpa was incorporated into laminC variants to study the network of interacting proteins at the nuclear lamina in live mammalian cells (Neumann‐Staubitz et al, 2022 ).…”
Section: Genetically Encoded Photo‐crosslinkersmentioning
confidence: 99%
“…The CDK1 complex targets several sites within different lamins, including lamin A/C (Thr19, Ser22, Ser392 and Ser404), lamin B1 (Ser23 and Ser393), and lamin B2 (Thr34, Ser37 and Ser405) (Figure 1C). All of these phosphorylation events contribute to lamin depolymerization and NEBD before the mitotic spindle assem-bles [20,[33][34][35]. Upon NEBD, NPC components are distributed between the endoplasmic reticulum (ER) and cytoplasm [36].…”
Section: Physiological Role Of Lamins and Their Regulation During Cel...mentioning
confidence: 99%
“…Rubporn et al [69] found that lamin A/C and several co-regulated proteins including KAP1 (TIF1β, TRIM28) were overexpressed in the A549 lung cancer cell line compared to MRC-5 normal lung fibroblast cells. Interestingly, Neumann-Staubitz et al [33] identified KAP1 as an interactor of the Ig-domain of lamin C using genetically encoded crosslinkers. KAP1 is involved in cell survival after DNA damage and its phosphorylation by ATM, ATR, and DNA-PK recruits KAP1 to DNA strand breaks [78].…”
Section: Role Of Lamin Dysregulation In Dna Damage Response Cell Cycl...mentioning
confidence: 99%